Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

Manipulating the organic-salt selectivity of N-2-hydroxyethylpiperazine based poly-ester-amide (PEA) membranes for antibiotic-NaCl separation - Qinghua Guo; Tao Shi; Lu Dai; Zhiguo Yan; Qun Chen; Man Xu; Yanbo Li (Desalination, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

An Interpretable Machine Learning Model for Predicting the Presence of Talaromycosis in HIV Patients Lacking Skin Lesions - Jiaguang Hu; Wenming He; Qun Tian; Yanqiu Lu; Peng Zhang; Jinyu Qin; Chuan Qin; Ying Wu; Cheng Huang; Xu Li; Luhuai Feng; Linghua Li; et al. (Mycopathologia, 2026)
Introduction The existing predictive models for talaromycosis in people living with HIV without skin lesions are limited by established risk factors and traditional statistical approaches. This study aims to develop an interpretable machine learning(ML) model for predicting the presence of talaromycosis in HIV patients without skin lesions and to validate its clinical applicability. Methods This retrospective multicenter study involved the analysis of electronic medical records from four tertiary hospitals in China, covering the period from 2010 to 2019. The training dataset comprised 1009 HIV patients with opportunistic infections, while external validation was conducted using data from 305 patients at an independent center. From an initial set of 36 variables, twelve key features were selected, including albumin, absolute lymphocyte count, hemoglobin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT ratio, C-reactive protein, white blood cell count, platelet count, peripheral or abdominal lymphadenopathy, CD4 + T-cell count, and age. Five ML algorithms were evaluated using tenfold cross-validation. Model performance was measured using the AUC, ACC, and F1-score. Calibration curves and decision curve analysis (DCA) were employed to assess the model’s reliability and clinical net benefit. The optimal model was subsequently implemented as a web-based tool. Results The Support Vector Machine (SVM) exhibited superior performance compared to other models, achieving an AUC of 0.809 (95% CI 0.778–0.838), an ACC of 0.714, and an F1-score of 0.689. External validation demonstrated enhanced performance metrics, with an AUC of 0.921 (95% CI 0.889–0.951), ACC of 0.853, and an F1-score of 0.819. DCA indicated a significant net clinical benefit across various risk thresholds, and calibration curves showed strong concordance between predicted and observed risks. Conclusion The interpretable SVM model effectively stratifies the risk of talaromycosis in people living with HIV without skin lesions in endemic regions, aligning with WHO recommendations for early diagnosis and treatment of priority fungal pathogens. Its integration into a web-based tool enhances clinical accessibility for early intervention in resource-constrained settings.

Evolutionary Pattern of Marine Stratocumulus Clouds Inferred from Satellite Snapshot Measurements - Yuan Li; Qi Liu; Zheng Qin; Zhenci Lu; Yanghui Peng; Qun Zheng (Advances in Atmospheric Sciences, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Engineered Escherichia coli Nissle 1917 carrying D-lactate dehydrogenase suppresses glioblastoma malignancy via gut-brain axis reprogramming - Qun Cao; Jiazheng Wang; Xuxiu Lu; Zhuo Li; Chenghui Guo; Chuanke Hou; Ping Li; Anjing Chen (Chemical Engineering Journal, 2026)

GABA-mediated neuroendocrine–immune regulation in Penaeus vannamei under low-salinity stress - Yuan Duan; Qun Zhao; Yifan Lu; Shiqi Li; Wenbo Wu; Erchao Li; Ardavan Farhadi (Fish & Shellfish Immunology, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Chronic social defeat stress accelerates lung cancer progression and induces hippocampal metabolic dysregulation in a duration-optimized comorbid model - Xiao-yu Liu; Shuo Wang; Yu-long Li; Jia Lu; Zheng Zhang; Jia-bin Zheng; Li-qun Jia (Metabolic Brain Disease, 2026)

Decarbonizing fossil-to-chemicals conversion: reliable real-time optimization under coupled chemical and carbon capture dynamics - Zhibo Zhang; Ze Li; Mengzhen Zhu; Yani Wang; Yibo Yuan; Honghua Qin; Jiarong Lu; Yaqian Li; Xin Zhou; Yibin Liu; Qun Zhang; Hao Yan; et al. (Journal of Cleaner Production, 2026)

N-doped biochar as a promising peracetic acid activator for sulfamethoxazole removal: Performance and mechanism - Zhuoran Li; Lu Han; Ran Wang; Jiaxuan Yu; Siqi Wang; Kaige Li; Qun Jiang; Jie Liu; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

Synergistic construction of high-performance oil-in-water emulsions by egg white protein-whey protein isolate dual-protein: achieving efficient utilization of bioactive substances - Yanli Wang; Yuanyuan Zhang; Erjiao Li; Haobo Jin; Yaqin Yang; Sadaqat Ali; Qun Lu; Zhaoxia Cai; Guofeng Jin; Long Sheng (Food Research International, 2025)

Sustainable thermochromic coatings for pavement cooling and carbon offset under climate change - Yujing Chen; Aimin Sha; Wei Jiang; Wenxiu Jiao; Yangsen Cao; Xinzhou Li; Xiaotong Du; Kui Hu; Qun Lu (Transportation Research Part D: Transport and Environment, 2025)

The topographic-related subsurface heat transport processes during the MJO propagation across the Maritime Continent - Kecheng Lu; Haibo Hu; Xiu-Qun Yang; Yiran Li; Peilong Yu; Kefeng Mao; Shengyi Qian; Ziyi Wang (Climate Dynamics, 2025)

Research on Magnetic Z-component Anomalies and Probabilistic Time Series Prediction Based on High-Density Geomagnetic Data in Southwest Yunnan - Lu-Qiang Sun; Tian Song; Chao-Qun Ma; Yan-Li Liu; Ming-Dong Zhang (Applied Geophysics, 2025)

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Aptamer-anchored hydrophobic nanopores for electrochemical/fluorescent dual-mode identification of pathogenic bacteria - Jiangxue Dong; Tianyi Lu; Yufan Zhang; Ming Su; Jingjing Wang; Yajie Fan; Yanlei Li; Hongyuan Yan; Shigang Shen; Qun Ma; Zhongfeng Gao (Chemical Engineering Journal, 2025)

Insight into interaction among soil microbial community, soil metabolomics and enzyme activity after long-term PAH stress - Liping Zheng; Qun Li; Junyang Du; Xiaosong Lu; Tingting Fan; Li Xu; Heidi qunhui Xie; Yangsheng Chen; Bin Zhao (Journal of Environmental Sciences, 2025)

A novel multimodal computer-aided diagnostic model for pulmonary embolism based on hybrid transformer-CNN and tabular transformer - Wei Zhang; Yu Gu; Hao Ma; Lidong Yang; Baohua Zhang; Jing Wang; Meng Chen; Xiaoqi Lu; Jianjun Li; Xin Liu; Dahua Yu; Ying Zhao; et al. (Physical and Engineering Sciences in Medicine, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Synthesis and multi-target evaluation of 2-(2-phenylethyl)/2,3-styrylchromone derivatives as potential anti-Alzheimer’s disease agents - JiaHao Lu; YingQI Qiu; ChenHao Zhao; Ai-Qun Wu; Haiou Jiang; Li-Qun Shen (Molecular Diversity, 2025)

Multi-omics analysis reveals potential mechanisms of diarrhetic shellfish toxin and fatty acid synthesis in marine harmful Prorocentrum - Danlin Zheng; Ligong Zou; Jian Zou; Qun Li; Songhui Lu (Journal of Hazardous Materials, 2025)

New insights into cold plasma-induced starch modification: A comparative analysis of microstructure and physicochemical properties in A-type and B-type starches - Zhenyu Liu; Xilu Zhang; Zerui Li; Yunhao Lu; Zhenghong Xu; Qun Shen; Yuanlong Chi (Food Chemistry, 2025)

Potential role of ovomucin in the “skeleton effect” of egg white thermal gel: Enhancing the cross-linking degree of egg white protein and the stability of the thermal gel network structure - Xin Liu; Bingxin Yang; Mingyue Lu; Lulu Ma; Jiaying Huo; Fang Geng; Qun Huang; Shijian Dong; Shugang Li (Food Hydrocolloids, 2025)

Potential mechanisms of ZiGongDing in treating HPV-induced cervical intraepithelial neoplasia: a network pharmacology and experimental verification study - Li Wan; Kan Chen; Xiaorong Ma; Lu Han; Qun Xie; Lihong Wang; Xinmei Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Mechanism of antimony oxidation and adsorption using immobilized Klebsiella aerogenes HC10 in soil - Qun Rong; Dingtian Lu; Kai Zhong; Shu Yang; Zhongyi Li; Chaolan Zhang (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Trifolium repens L. recruits root-associated Microbacterium species to adapt to heavy metal stress in an abandoned Pb-Zn mining area - Xin-qi Yuan; Yi-yi Liu; Si-chen Wang; Ya-qi Lu; Yin-jie Li; Jin-quan Chen; Chang-qun Duan (Science of The Total Environment, 2024)

An investigation of a self-powered low-frequency nonlinear vibration isolation system - Ze-Qi Lu; Rong-Biao Hao; Dao Wu; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Simultaneous efficient evaporation and stable electricity generation enabled by a wooden evaporator based on composite photothermal effect - Wang Lu; Dexing Jiang; Zhaofeng Wang; Xu Zhang; Qun Ding; Zhuo Zhang; Xiaowei Liu; Long Bai; Zhiguo Li; Yang Liu (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Urbanization impact on meteorological condition and O3 concentration under past and future climates scenarios over the Greater Bay Area in Southern China - Qun Wang; Yiang Chen; Xingcheng Lu; Guangzhao Chen; Zhenning Li; Meng Cai; Chao Ren; Jimmy C.H. Fung (Atmospheric Environment, 2024)

miR-575/RIPK4 axis modulates cell cycle progression and proliferation by inactivating the Wnt/β-catenin signaling pathway through inhibiting RUNX1 in colon cancer - Qun Wang; Weijun Lu; Li Lu; Ruopu Wu; Dongde Wu (Molecular and Cellular Biochemistry, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

A novel derivative synchronous fluorescence method for the rapid, non-destructive and intuitive differentiation of denitrifying bacteria - Huang-Zhou Lv; Jinliang Chen; Yan Zhao; Yu Li; Shuo-Hui Cao; Wei-Peng Cai; Liang Shen; Yinghua Lu; Yao-Qun Li (Journal of Environmental Management, 2024)

Membrane Trafficking-Related Genes Predict Tumor Immune Microenvironment and Prognosis in Colorectal Cancer - Zhou Ding; Lu Han; Qun Zhang; Jing Hu; Li Li; Xiaoping Qian (Biochemical Genetics, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Effect of land surface parameters on meteorology and ozone air quality simulations in the Great Bay Area, China - Qun Wang; Yiang Chen; Tung Fung; Zhenning Li; Yeqi Huang; Michael Mau Fung Wong; Xingcheng Lu (Atmospheric Environment, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

Integration of hyperspectral imaging, non-targeted metabolomics and machine learning for vigour prediction of naturally and accelerated aged sweetcorn seeds - Tingting Zhang; Long Lu; Ni Yang; Ian D. Fisk; Wensong Wei; Li Wang; Jing Li; Qun Sun; Rensen Zeng (Food Control, 2023)

Selective hydrogenation of acetylene on carbon-encapsulated Ni-Co-Cu trimetallic nanoparticles: Synergizing electronic effects and spatial confinement - Shihong Zhou; Chenyang Lu; Yi Bi; Cailong Zhou; Qun Li; Luxi Tan; Lichun Dong (Chemical Engineering Journal, 2023)

Discrimination of Schizothorax grahami (Regan, 1904) Stocks Based on Otolith Morphology - Yang Zhou; Li Xu; Zhongtang He; Weijie Cui; Qun Lu; Jianguang Qin; Shengqi Su; Tao He (Fishes, 2023)
Otoliths grow throughout a fish’s life and are important for identifying fish stocks and fish age. This study aims to differentiate different stocks of Schizothorax grahami (Regan, 1904) in the Chishui River, an upper reach of the Yangtze River, by otolith morphology. The otolith morphology of S. grahami from three different river sections was analyzed using the Shape Index, Fourier coefficients, and wavelet coefficients. The composite discrimination success rate of the Shape Index was 59.7%, and it was difficult to distinguish in the scatter plots. In contrast, canonical principal coordinate scatter plots clearly showed three distinguished stocks. The above results indicate that otolith morphology can discriminate between stocks in plateau endemic fish, and several S. grahami stocks may be separately managed in the Chishui River.

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Ridge tillage increased halophyte fine root production and turnover rates by altering soil properties in an abandoned farmland in northwest China - Xu Zheng; Chao-qun Chen; Lu-hua Li; Jia-ping Wang (Rhizosphere, 2023)

Antioxidant and anti-inflammatory activities of rape bee pollen after fermentation and their correlation with chemical components by ultra-performance liquid chromatography-quadrupole time of flight mass spectrometry-based untargeted metabolomics - Huifang Zhang; Xiaoling Zhu; Qian Huang; Li Zhang; Xiaohua Liu; Rui Liu; Qun Lu (Food Chemistry, 2023)

Acrylamide in food: Occurrence, metabolism, molecular toxicity mechanism and detoxification by phytochemicals - Fangfang Yan; Li Wang; Li Zhao; Chengming Wang; Qun Lu; Rui Liu (Food and Chemical Toxicology, 2023)

Carbon-confined Cu-Pd alloy nanoparticles as high-performance catalysts for acetylene selective hydrogenation - Chenyang Lu; Shihong Zhou; Wenyu Zhou; Cailong Zhou; Qun Li; Aonan Zeng; Anjie Wang; Luxi Tan; Lichun Dong (Chemical Engineering Journal, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

On the Generation and Evolution of Internal Solitary Waves in the Andaman Sea - Yujun Yu; Tao Xu; Jinhu Wang; Shuya Wang; Qun Li; Jing Meng; Xu Chen; Kexiao Lu; Guixia Wang (Journal of Ocean University of China, 2023)

Identification and characterization of two long-type peptidoglycan recognition proteins, PGRP-L1 and PGRP-L2, in the orange-spotted grouper, Epinephelus coioides - Jing Hou; Wei Hao; Min Chang Li; Zhen Gan; Shan Nan Chen; Yi Shan Lu; Li Qun Xia (Fish & Shellfish Immunology, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

Alterations to cognitive abilities and functional networks in rats post broad-band intense noise exposure - Xiao-Min Xu; Yu-Qun Zhang; Feng-Chao Zang; Chun-Qiang Lu; Li-Jie Liu; Jian Wang; Richard Salvi; Yu-Chen Chen; Gao-Jun Teng (Brain Imaging and Behavior, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

GC–MS fingerprints of essential oils from agarwood grown in wild and artificial environments - Cheng-piao Tian; Xing-dong Yao; Jia-hao Lu; Li-qun Shen; Ai-qun Wu (Trees, 2021)

Ubiquitination of p21 by E3 Ligase TRIM21 Promotes the Proliferation of Human Neuroblastoma Cells - Fan Wang; Zerui Wu; Qun Li; Zhihui Ni; Chengde Wang; Jianglong Lu (NeuroMolecular Medicine, 2021)

Influence of loading rates under true triaxial stress on the mechanical properties and rockburst characteristics of granite - Zhanjin Li; Lu Zhang; Qun Li; Haojie Cheng (Arabian Journal of Geosciences, 2021)

Effects of temperature on the growth and carbohydrate production of three benthic dinoflagellate species from Hainan Island, South China Sea - Zhen Wu; Hua Zhang; Qun Li; Lei Cui; Heng Chen; Songhui Lu (Ecotoxicology, 2021)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Defining the Boundaries of Urban Built-up Area Based on Taxi Trajectories: a Case Study of Beijing - Yuanfu Li; Qun Sun; Xiaolin Ji; Li Xu; Chuanwei Lu; Yunpeng Zhao (Journal of Geovisualization and Spatial Analysis, 2020)

Dissecting the genetic basis of fiber quality and yield traits in interspecific backcross populations of Gossypium hirsutum × Gossypium barbadense - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Baocai Zhang; Qun Ge; Muhammad Jamshed; Quanwei Lu; Shaoqi Li; Xianghui Xiang; Juwu Gong; Wankui Gong; et al. (Molecular Genetics and Genomics, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

The mediated role of complement C3 in PM2.5 exposure and type 2 diabetes mellitus: an elderly panel study in Beijing, China - Yuanren Tong; Lu Pei; Kai Luo; Meiduo Zhao; Jing Xu; Ang Li; Runkui Li; Mingan Yang; Qun Xu (Environmental Science and Pollution Research, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Spatial variation in the effects of air pollution on cardiovascular mortality in Beijing, China - Wenjing Li; Lu Pei; Ang Li; Kai Luo; Yang Cao; Runkui Li; Qun Xu (Environmental Science and Pollution Research, 2019)

Alterations in Normal Aging Revealed by Cortical Brain Network Constructed Using IBASPM - Wan Li; Chunlan Yang; Feng Shi; Qun Wang; Shuicai Wu; Wangsheng Lu; Shaowu Li; Yingnan Nie; Xin Zhang (Brain Topography, 2018)

Genetic analysis of the fiber quality and yield traits in G. hirsutum background using chromosome segments substitution lines (CSSLs) from Gossypium barbadense - Lixue Guo; Yuzhen Shi; Juwu Gong; Aiying Liu; Yunna Tan; Wankui Gong; Junwen Li; Tingting Chen; Haihong Shang; Qun Ge; Quanwei Lu; Jie Sun; et al. (Euphytica, 2018)

Improved plane layout of stabilizing piles based on the piecewise function expression of the irregular driving force - Wen-qiang Liu; Qun Li; Jian Lu; Chang-dong Li; Wen-min Yao; Jiang-bo Zeng (Journal of Mountain Science, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Polyol monoterpenes isolated from Chenopodium ambrosioides - Shu-Qun Hou; Yan-Hong Li; Xiang-Zhong Huang; Rong Li; Huai Lu; Kai Tian; Rong-Sheng Ruan; Yu-Kui Li (Natural Product Research, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Genetic alterations of δ-catenin/NPRAP/Neurojungin (CTNND2): functional implications in complex human diseases - Qun Lu; Byron J. Aguilar; Mingchuan Li; Yongguang Jiang; Yan-Hua Chen (Human Genetics, 2016)

The Synergistic Effect of Serine with Selenocompounds on the Expression of SelP and GPx in HepG2 Cells - Qin Wang; Li-cui Sun; Yi-qun Liu; Jia-xi Lu; Feng Han; Zhen-wu Huang (Biological Trace Element Research, 2016)

Genomic characterization of symbiotic mycoplasmas from the stomach of deep‐sea isopod bathynomus sp - Yong Wang; Jiao‐Mei Huang; Shao‐Lu Wang; Zhao‐Ming Gao; Ai‐Qun Zhang; Antoine Danchin; Li‐Sheng He (Environmental Microbiology, 2016)
Deep‐sea isopod scavengers such as Bathynomus sp. are able to live in nutrient‐poor environments, which is likely attributable to the presence of symbiotic microbes in their stomach. In this study we recovered two draft genomes of mycoplasmas, Bg1 and Bg2, from the metagenomes of the stomach contents and stomach sac of a Bathynomus sp. sample from the South China Sea (depth of 898 m). Phylogenetic trees revealed a considerable genetic distance to other mycoplasma species for Bg1 and Bg2. Compared with terrestrial symbiotic mycoplasmas, the Bg1 and Bg2 genomes were enriched with genes encoding phosphoenolpyruvate‐dependent phosphotransferase systems (PTSs) and sodium‐driven symporters responsible for the uptake of sugars, amino acids and other carbohydrates. The genome of mycoplasma Bg1 contained sialic acid lyase and transporter genes, potentially enabling the bacteria to attach to the stomach sac and obtain organic carbons from various cell walls. Both of the mycoplasma genomes contained multiple copies of genes related to proteolysis and oligosaccharide degradation, which may help the host survive in low‐nutrient conditions. The discovery of the different types of mycoplasma bacteria in the stomach of this deep‐sea isopod affords insights into symbiotic model of deep‐sea animals and genomic plasticity of mycoplasma bacteria.

Identification of QTLs for seed quality traits in rapeseed (Brassica napus L.) using recombinant inbred lines (RILs) - Xian-Qun Huang; Tuan Huang; Guo-Zuo Hou; Li Li; Yan Hou; Yun-Hai Lu (Euphytica, 2016)

Effect of lipopolysaccharide on the hemocyte apoptosis of Eriocheir sinensis - Hai-sheng Xu; Sun-jian Lyu; Jie-hao Xu; Bin-jie Lu; Jing Zhao; Song Li; Yi-qun Li; Yu-yin Chen (Journal of Zhejiang University-SCIENCE B, 2015)

The acute effects of outdoor temperature on blood pressure in a panel of elderly hypertensive patients - Renjie Chen; Jianxiong Lu; Qun Yu; Li Peng; Dandan Yang; Cuicui Wang; Haidong Kan (International Journal of Biometeorology, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Successful Treatment of a Necrotizing Fasciitis Patient Caused by Mucor indicus with Amphotericin B and Skin Grafting - Yijin Luo; Fanqin Zeng; Xiaowen Huang; Qun Li; Guozhen Tan; Liyan Xi; Changming Lu; Qing Guo (Mycopathologia, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Blockade of high-mobility group box-1 ameliorates acute on chronic liver failure in rats - Xun Li; Li-Kun Wang; Lu-Wen Wang; Xiao-Qun Han; Fan Yang; Zuo-Jiong Gong (Inflammation Research, 2013)

Synthesis and insect antifeedant activity of stilbene derivatives against Brontispa longissima Larvae - Ying-Qian Liu; Xiao-Jing Li; Chun-Yan Zhao; Yan Lu; Wen-Qun Li; Zhen-Ling Liu; Gang Feng; Liu Yang (Medicinal Chemistry Research, 2013)

Effect of advanced glycosylation end products (AGEs) on proliferation of human bone marrow mesenchymal stem cells (MSCs) in vitro - Yi-qun Lu; Yan Lu; Hui-juan Li; Xing-bo Cheng (In Vitro Cellular & Developmental Biology - Animal, 2012)

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China - Sheng-Ping Hu; Hui Li; Feng-Huan Zhang; Li-Qun Huang; Yan Lu (Biochemical Genetics, 2011)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)